Key attributes of successful research institutes. - Frank Bradke; Aidan Maartens; Sarah A Teichmann (PLoS Biology)
Science does not take place in a vacuum: The physical and social workplace has a profound influence on scientific discoveries. Everyone at a research institute can contribute to its scientific output and productivity, from faculty research groups to facilities and platforms staff to administration and corporate services. Although the researchers addressing exciting scientific questions are key, their efforts can be fostered and directed by the overarching strategy of the institute, interconnection with facilities and platforms, and strong and directed support of the administration and corporate services. Everybody counts and everybody should be empowered to contribute. But what are the characteristics that make scientific organizations and their people flourish? This Essay looks at the structure and culture of successful research institutes, laying out different operational strategies and highlighting points that need be taken into consideration during their implementation.